2019
DOI: 10.1155/2019/8479680
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine Formula Shenling Baizhu San Ameliorates High-Fat Diet-Induced NAFLD in Rats by Modulating Hepatic MicroRNA Expression Profiles

Abstract: Objective. The purpose of present study was to investigate the potential mechanism underlying the protective effect of Shenling Baizhu San (SLBZS) on nonalcoholic fatty liver disease (NAFLD) by microRNA (miRNA) sequencing. Methods. Thirty male Wistar rats were randomly divided into a normal control (NC) group, a high-fat diet (HFD) group, and an SLBZS group. After 12 weeks, the biochemical parameters and liver histologies of the rats were assessed. The Illumina HiSeq 2500 sequencing platform was used to analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…So, in ApoE -/mice under HFD that develop advanced atherosclerosis and fatty liver, a signi cant increase of miR-155-5p levels not only was observed in aorta but also in liver and exosomes-enriched vesicles. Accordingly, with our results, hepatic miR-155-5p is upregulated in HFD-induced non-alcoholic fatty liver disease (NAFLD) in rats 44 and in non-alcoholic steatohepatitis (NASH) mouse models 45 . Indeed, miR-155 plays a key role in the liver lipid metabolism and its de ciency reduces steatosis and brosis 46 .…”
Section: Discussionsupporting
confidence: 68%
“…So, in ApoE -/mice under HFD that develop advanced atherosclerosis and fatty liver, a signi cant increase of miR-155-5p levels not only was observed in aorta but also in liver and exosomes-enriched vesicles. Accordingly, with our results, hepatic miR-155-5p is upregulated in HFD-induced non-alcoholic fatty liver disease (NAFLD) in rats 44 and in non-alcoholic steatohepatitis (NASH) mouse models 45 . Indeed, miR-155 plays a key role in the liver lipid metabolism and its de ciency reduces steatosis and brosis 46 .…”
Section: Discussionsupporting
confidence: 68%
“…Indeed, the deletion of miR-155 in mice prevented diet-induced obesity, improved insulin sensitivity, and abrogated adipocyte hypertrophy and adipose tissue inflammation [ 43 ]. Moreover, the reduction in miR-155 increases the expression of genes involved in brown adipogenesis, lipolysis, and energy release, which could synergize to improve fat metabolism [ 44 , 45 , 46 , 47 ]. Our results suggest that miR-155-5p might promote the simultaneous development of several pathophysiological processes in different organs, such as vascular and hepatic insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [ 22 ] confirmed that Yangzheng Sanjie decoction containing serum could inhibit the proliferation and induce the apoptosis of gastric cancer cells mediated by miR-7-targeting EGFR (encoding the epidermal growth factor receptor). Pan et al [ 23 ] investigated the potential mechanism underlying the protective effect of Shenling Baizhu San on nonalcoholic fatty liver disease by microRNA sequencing and identified 28 differentially expressed miRNAs. To enrich the evidence for SJZT's antitumor effect at the level of posttranscriptional gene regulation, we performed miRNA sequencing and found 33 miRNAs that displayed differential expression patterns in the SJZT group compared with Model group, demonstrating a potent effect of SJZT in globally altering tumor miRNA expression.…”
Section: Discussionmentioning
confidence: 99%